(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes the genetic foundations, the author’s expressive style, and the artistic-aesthetic concept in the essays "Yalangto‘shbiy bahodir", "Olloyoron kabi yuksal, Urgutim!", and "Bo‘saga" written by the renowned Uzbek writer and Honored Cultural Worker of Uzbekistan, Asad Dilmurod.